2013
DOI: 10.1002/jgrb.50178
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake clusters in southern California II: Classification and relation to physical properties of the crust

Abstract: [1] This is a second paper in a study of statistical identification and classification of earthquake clusters using a relocated catalog of 1981-2011 seismicity in southern California and synthetic catalogs produced by the Epidemic Type Aftershock Sequence model. Here we focus on classification of event families-statistically significant clusters composed of foreshocks, mainshocks, and aftershocks-that are detected with the methodology discussed in part I of the study. The families are analyzed using their repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
145
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(168 citation statements)
references
References 21 publications
13
145
1
Order By: Relevance
“…We find that pronounced event-event triggering is only observable in the presence of large-scale imperfections such as a notch or inclusion in the sample. Triggering cascades tend to propagate away from the imperfections, and large cascades have a more swarmlike topology as observed for earthquakes in areas of high heat flow [29]. The triggered events typically have a focal mechanism more similar to their trigger than expected by chance, and they follow a GR distribution with a significantly lower b value than observed for background events (events without a trigger)-both features have also been reported for earthquakes [10,30].…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…We find that pronounced event-event triggering is only observable in the presence of large-scale imperfections such as a notch or inclusion in the sample. Triggering cascades tend to propagate away from the imperfections, and large cascades have a more swarmlike topology as observed for earthquakes in areas of high heat flow [29]. The triggered events typically have a focal mechanism more similar to their trigger than expected by chance, and they follow a GR distribution with a significantly lower b value than observed for background events (events without a trigger)-both features have also been reported for earthquakes [10,30].…”
mentioning
confidence: 62%
“…week ending 11 AUGUST 2017 068501-3 values indicate that the cascades tend to follow a swarmlike structure and that the triggering process does not obey a simple branching process as often assumed [29]. Another feature of the underlying triggering process is that the distribution of 3D rotation angles δ between the trigger and triggered event is typically smaller than for random events, see Fig.…”
Section: Prl 119 068501 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 93%
See 2 more Smart Citations
“…We note that Zaliapin and Ben-Zion (Zaliapin and Ben-Zion 2013a) have observed that for earthquake sequences in southern California DM follows an almost uniform distribution in the range [0,2] with an exponential tail for larger values of DM, thus supporting the value hDMi = 1.1 which has been found (Zaliapin and Ben-Zion 2013a) in the observed seismicity of southern California. They have also identified (Zaliapin and Ben-Zion 2013b) that there exist two basic types of earthquake clustering: the burst-like sequences which are consistent with highly brittle behaviour and the swarm-like sequences consistent with mixed brittle-ductile behaviour. The latter sequences result in smaller DM values than those of the former.…”
Section: A Model For the Explanation Of Båth Lawmentioning
confidence: 99%